Simple LASER Tracking Algorithm Using Programmable System on Chip (PSoC) for Visible Light Communication (VLC) - Shaher Dwik; Somasundaram, Natarajan; al Musalli, Tarek; Amaya, Mohammad (Optical memory & neural networks, 2022)
This paper presents a simple LASER tracking algorithm that can be used for Visible Light Communication (VLC) which is a new technology that uses the visible light (380–780 nm) as a carrier for the data. Recently, VLC has attracted a high attention because it has the potential transmissions at very-high data rates. To attain a good communication in VLC, both the transmitter and receiver must be on one line, otherwise the whole system will fail. The proposed algorithm has been implemented using Two-Dimensional Position Sensitive Detector (PSD) and Programmable System on Chip 3 (PSoC3). The PSD is an optoelectronic sensor which is used to measure the radiation spot position with an ability to sense the position in one or two dimensions. The used PSD sensor consists of two-dimensional array of photodiodes and it has four output photocurrents which vary with the position of incident radiation on the surface. To validate the proposed algorithm, MATLAB is used to simulate the PSD using its modeling equations. Solidworks software tool is also used to design and simulate the gimbal. The hardware implementation is done for the validation purpose by using the PSoC which occupies minimum board space, consumes less power, provides high efficiency and reduces system cost.